The arbitrariness of criminal punishment (the example of fine) - V. M. Stepashin (Правоприменение, 2018)
The subject. The paper deals with the problem of arbitrariness of criminal punishment in case of replacement of fine with other types of criminal penalties.The purpose of the paper is to identify the criteria to replace the fine to more severe kind of punishment.Methodology. The author uses the methods of analysis and synthesis, as well as dialectic approach. The formal-legal interpretation of the Criminal Codes and of the Russian Federation researches of familiar criminalists is also used.The main results and scope of their application. The arbitrariness of repression as its indicator means the possibility of changing the quality, quantity and (or) intensity of repression depending on the convicted person's compliance with the imposed regime, including the replacement of the assigned measure of state coercion with a more severe one.The author proposes a new version of pt. 5 of art. 46 of the Criminal Code of the Russian Federation. A new model of the consequences of non-payment of a penalty involves the observance of several conditions: 1) every sanctions, including penalty of a fine, should be submitted to the alternative punishment; 2) every sanction, including a penalty of fine and imprisonment, should be submitted to the "intermediate" punishment; 3) selecting the replacement of punishment should be due to unpaid fines and to provide a factual and not a formal toughening of punishment; 4) should establish the possibility of replacing the fine with imprisonment in proportion to the unpaid amount of the fine.The results of research may be used as the basis of correction of the Criminal Code of the Russian Federation and judicial practice. The paper may also inspire new researches concerning replacement of criminal punishment.Conclusions. The current system of replacing the fine does not correspond to the idea of saving repression. The new scheme of replacement of criminal punishment proposed in the paper is less arbitrary.